2008
DOI: 10.1158/0008-5472.can-07-6484
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Agonist Therapy Enhances CD8 Infiltration and Decreases Immune Suppression in the Tumor

Abstract: Acquisition of full T-cell effector function and memory differentiation requires appropriate costimulatory signals, including ligation of the costimulatory molecule OX40 (TNFRSF4, CD134). Tumors often grow despite the presence of tumor-specific T cells and establish an environment with weak costimulation and immune suppression. Administration of OX40 agonists has been shown to significantly increase the survival of tumor-bearing mice and was dependent on the presence of both CD4 and CD8 T cells during tumor-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 54 publications
9
145
2
Order By: Relevance
“…Some authors have reported tumor-infiltrating CD11b 1 CD11c 1 cells expressing OX40 [20], while others did not detect OX40 expression on CD11b 1 cells, even if OX86 systemic administration could indirectly reduce their frequency in tumors [21]. Tumor-infiltrating macrophages (CD45 1 CD11b 1 F4/80 1 ), representing the vast majority of immune infiltration in our tumor model, neither expressed OX40 nor was their IL-10 secretion affected by OX40 stimulation (data not shown).…”
Section: Intratumoral Ox40 Triggering Significantly Reduces Il-10 Secmentioning
confidence: 56%
See 1 more Smart Citation
“…Some authors have reported tumor-infiltrating CD11b 1 CD11c 1 cells expressing OX40 [20], while others did not detect OX40 expression on CD11b 1 cells, even if OX86 systemic administration could indirectly reduce their frequency in tumors [21]. Tumor-infiltrating macrophages (CD45 1 CD11b 1 F4/80 1 ), representing the vast majority of immune infiltration in our tumor model, neither expressed OX40 nor was their IL-10 secretion affected by OX40 stimulation (data not shown).…”
Section: Intratumoral Ox40 Triggering Significantly Reduces Il-10 Secmentioning
confidence: 56%
“…Conversely, in a murine tumor model, others have shown that CD25 1 -cell depletion and IL-10 receptor blockade exert distinct, though partially overlapping, effects in suppressing DC activation and anti-tumor CD8 1 response [13]. Even if a Foxp3-directed, rather than CD25-directed, Treg-cell depletion may provide more reliable results about the functional redundancy of Treg cells and IL-10, it is likely that Treg cells are not the only source of IL-10 at the tumor site [13] and that sole IL-10 receptor blockade cannot recapitulate the efficient anti-tumor activity of combination therapies [35,36], of the sole OX40 triggering [3,21] or of Foxp3-targeted Treg-cell depletion, when combined to vaccination [39] or even as single treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Hence, it is reasonable that an OX40 agonist is responsible for tumor regression via restoring the ability of CD8 ĂŸ T cells. 55,56 A phase I study performed in melanoma patients with anti-OX40 mouse monoclonal antibody confirmed its potent antitumor property. 57 It is interesting to combine coinhibitory inhibitors and costimulatory factors to completely activate the anergic T cells in tumors.…”
Section: Combination Strategiesmentioning
confidence: 94%
“…These experiments used the MCA205 sarcoma cell line as previously described. 21 Control RatIg antibody was purchased from Sigma (St Louis, MO) and the rat anti-OX40 antibody (OX86) was produced in the laboratory from hybridomas and affinity-purified over protein G columns. All animal protocols were approved by the Institution's Animal Care and Use Committee.…”
Section: Animals Cell Lines and In Vivo Antibodiesmentioning
confidence: 99%
“…[21][22][23] Therefore, we hypothesize that the development of a mature tumour environment limits the efficacy of aOX40 therapy, by establishing inflammatory resolution in the tumour. We demonstrated that following aOX40 therapy of established tumours there is an influx of CD8 T cells to the tumour, associated with a transient control of tumour growth, which was accompanied by an altered profile of tumour macrophages.…”
Section: Introductionmentioning
confidence: 99%